A NEW MULTIDIMENSIONAL GRAPHICAL APPROACH FOR MATHEMATICS AND PHYSICS - Ruiz Estrada, Mario Arturo (Malaysian Journal of Science, 2012)
This research proposes a serial of new mathematic and physics theoretical framework under a multidimensional focus. The main objective of this paper is to motivate scientists in various areas to use multidimensional coordinate spaces to complement the 2-Dimensional and 3-Dimensional coordinate systems. Additionally, this paper is divided into two large sections that is the mathematic and physics section respectively. Finally, these two sections will be sectioned into eight different elemental theoretical frameworks. The mathematic section is divided into five elemental theoretical frameworks: (i) the idea on zero and infinity in multidimensional coordinate systems; (ii) the megasfinity; (iii) multidimensional partial differentiation; (iv) possibility of plotting matrices on multidimensional coordinate systems; and (v) the global crisis smash graphic effect model (GCSGE-Model). The physics section is divided into three elemental theoretical frameworks: (i) the theory of empty spaces; (ii) the mega time-space continuum; (iii) the Megasverses. (Keywords: Multidimensional graphs, multidimensional graphical modeling, multidimensional coordinate spaces.)